The diagnostic utility of bone marrow biopsies performed for the investigation of fever and/or cytopenias in HIV-infected adults at Groote Schuur Hospital. - Van Schalkwyk, Willem Adendorff (Division of Clinical Haematology, 2014)
This is a retrospective review of the results of consecutive bone marrow biopsies performed at our institution over a three year period on HIV positive patients for the investigation of fever and cytopenias. Clinical data, haematological parameters, morphology of bone marrow biopsy, Ziehl-Neelsen staining and microbiological culture results were analyzed. The aim of the study was to determine the diagnostic yield of this investigation.